2018
DOI: 10.22214/ijraset.2018.1391
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Complete Color Critical Graphs

Abstract: PAN Critical graphs). In this paper, we investigate the properties of these critical graphs. We also investigate the locally critical elements of graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Therefore, evaluation of some clinical, haematological and serum biochemistry analytes helps to determine the presence of damage and/or the severity of damage in target organs (Gülersoy & Ekici, 2022). It was reported that Na and K concentrations decrease in dogs with diarrhoea due to vomiting, diarrhoea and inflammatory changes in the gastric and intestinal mucosa (Kumar & Kumar, 2017). Moreover, it was reported that mal-nutrition, septicemia and stress-induced activation of catecholamines cause electrolyte imbalances such as hypokalemia, hyponatremia and hypochloremia in dogs with CPV (Kalli et al, 2010).…”
Section: Receiver Operating Characteristic Analysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, evaluation of some clinical, haematological and serum biochemistry analytes helps to determine the presence of damage and/or the severity of damage in target organs (Gülersoy & Ekici, 2022). It was reported that Na and K concentrations decrease in dogs with diarrhoea due to vomiting, diarrhoea and inflammatory changes in the gastric and intestinal mucosa (Kumar & Kumar, 2017). Moreover, it was reported that mal-nutrition, septicemia and stress-induced activation of catecholamines cause electrolyte imbalances such as hypokalemia, hyponatremia and hypochloremia in dogs with CPV (Kalli et al, 2010).…”
Section: Receiver Operating Characteristic Analysis Resultsmentioning
confidence: 99%
“…In the present study, the serum Na and K concentrations of the dogs with infectious diarrhoea were lower than that of the Control Group ( p < 0.05) (Table 2). This finding is related to vomiting and diarrhoea caused by gastroenteritis (Kumar & Kumar, 2017). Increased BUN and CR concentrations were reported as a result of dehydration due to vomiting and diarrhoea associated with gastroenteritis, and they were reported to be useful predictors of dehydration (Hoxha et al., 2014).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This color mixing is an important process widely applied in several fields. There are various kinds of color mixing strategies that can be seen in the literature [3][4][5][6][7][8][9][10][11][12][13][14][15][16] and [17][18][19][20][21][22][23][24][25]. Many industries and research organizations are involved in designing a color mixing system in order to increase productivity and reduce human efforts.…”
Section: Introductionmentioning
confidence: 99%
“…After Appel and Haken gave a computer verification proof of the Four Color Conjecture, research focus was shifted to coloring that satisfies some specified property [5]. The coloring plays an important role in the combinatorial optimization problems and critical graphs (optimal graphs) are crucial in the Chromatic number Theory [7,8,9,10,11]. Several studies were made in applying graph theory parameters to Roman defense strategy [1,2,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%